Continuing Professional Education in Australia A Tale of Missed Opportunities - Brennan, Barrie (Springer Nature Singapore : Imprint: Springer, 2016)
This book offers a history of Continuing Professional Development (CPD) in the Australian context. It presents an approach that links the development of CPD to a series of 'missed opportunities' and the identification of three key themes (mandatory CPD, competencies and regulation/registration) as well as with national regulation for select health professions. It not only relates the evolution of CPD in Australia but also serves as a guide to examining the situation in other countries and the emergence of CPD in individual professions. CPD has been provided for many decades, but it has not been rated as a 'high priority' or a key area of provision and has not been the focus of discussions or disputes in the higher education sector or in vocational education circles. Nevertheless in describing CPD's development, evidence is presented that CPD has made a significant contribution to the broad field of vocational education.